2010
DOI: 10.1007/s00268-010-0720-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Somatic Mutations Improves the Accuracy of Thyroid Fine‐needle Aspiration Biopsy

Abstract: BackgroundThyroid fine-needle aspiration (FNA) biopsy is indeterminate or suspicious in up to 30% of cases and these patients are commonly subjected to at least a diagnostic hemithyroidectomy. If malignant on histology, a completion thyroidectomy is usually performed, which may be associated with higher morbidity. To determine the clinical utility of genetic testing in thyroid FNA biopsy, we conducted a prospective clinical trial.MethodsFour hundred seventeen patients with 455 thyroid nodules were enrolled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
157
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 23 publications
6
157
1
Order By: Relevance
“…10,12 Moreover, we detected 10/48 mutated samples (21%) with a higher incidence of RAS variants in comparison with previous reports in Thy 3 patients. 10,16 In addition to establishing the evident advantages of HRM prescreening in terms of time and economic improvement, this pilot study confirmed the accuracy of the proposed method.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…10,12 Moreover, we detected 10/48 mutated samples (21%) with a higher incidence of RAS variants in comparison with previous reports in Thy 3 patients. 10,16 In addition to establishing the evident advantages of HRM prescreening in terms of time and economic improvement, this pilot study confirmed the accuracy of the proposed method.…”
Section: Discussionsupporting
confidence: 55%
“…Approximately 20% of patients with FNAB biopsy showing indeterminate cytological features have thyroid cancer revealed on histological examination and may require a complete thyroidectomy. 12 Typical genetic alterations are described for most differentiated thyroid cancers, which constitute approximately 90% of all cases. 25 In clinical management, given the importance of a correct classification of cytologically undefined FNAB, rapid and accurate methods are needed to screen the most common somatic mutations in a series of known oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…TRK rearrangements may also be added to this panel. Presence of BRAF, RAS, RET/PTC, PAX8-PPAR␥ and TRK in FNAB samples correlated with malignancy in 97% of cases [196,197,212]. Therefore, detection of any mutation of this panel is a strong predictor for thyroid cancer.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 98%
“…However, its results may not always be conclusive. Patients with non-diagnostic results in two consecutive thyroid FNABs and some patients with indeterminate follicular lesions are candidates for thyroid surgery, although only 10-20% of these tumours turn out to be cancerous [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, these nodules are benign [2,3]. In 5% of fine-needle aspiration biopsies a thyroid cancer is diagnosed [4,5]. Standard pre-operative diagnostic tests of nodular goitre are mainly based on two investigations: a thyroid ultrasound (US) and ultrasound-guided fine-needle aspiration biopsy (US-FNAB).…”
Section: Introductionmentioning
confidence: 99%